A novel train control approach to avoid rear-end collision based on geese migration principle. (January 2017) - Wang, Junfeng; Wang, Jungang; Roberts, Clive; Chen, Lei; Zhang, Yong
Highlights: Geese migration principle is applied to supervise trains interval. Not only ATP but CTC are used to parallel monitor trains interval. Parallel monitoring can avoid effectively accidents of rear-end collision. The safety and performance of train control system will be improved. Abstract: For current train interval control based on Automatic Train Protection (ATP) system, when the ATP outputs erroneous commands or is unable to realize fail-safety in the case of ATP equipment failure, train rear-end collision will be likely to happen. The "7.23" train accident happened in 2011 in China is a typical example. A method of parallel control of train interval by using both Centralized Traffic Control (CTC) and ATP, or simplified as CTC&ATP based interval control, is proposed. By adding some hardware and software into the existing CTC system, the CTC can monitor train following interval and give early warning. In this method CTC based interval control works together with the existing ATP, the monitoring of train interval will be doubled. This method can improve the safety of train interval control, compensate for the lack of control when the autonomic control fails, and avoid common cause failures. The geese migration theory is used in the proposed method, in which the CTC controls the train interval as the goose line, while the ATP controls the train interval as goose interval. This paper analyzes the necessity and feasibility of the proposed CTC based train interval pre-warning and control method, and explains the basic structure of the system, data acquisition, train following interval calculation, pre-warning rules and implementation of the system. The CTC based train interval calculation model was established and the warning distances under different speed were calculated. The safety and reliability of CTC&ATP train interval control system were analyzed.